Suminto A. Sayuti Menulis untuk Pulang: Creative process amid a departing literary field - Ridlo, Muhammad Rasyid; Wiyatmi , Wiyatmi; Ilma , Awla Akbar; Hakim , Arif Rohman (BAHASTRA, 2026)
This study reveals that Suminto A. Sayuti’s rural habitus functions not merely as a biographical backdrop, but as a strategy of differentiation that actively transforms crafted experiences, oral literacy, and wayang traditions into symbolic authority within the post-digital literary landscape. An analysis of the poetry collection Ketika Diri adalah Kepulangan dan Keberangkatan (2023), in-depth interviews, and publisher statements indicates that the poet’s liminal position—neither fully at the center nor the periphery—is not a sign of marginality, but rather a space of agency that enables a productive resistance to the logic of virality, instant poetry, and algorithmic simulation. Aesthetic strategies emphasizing lengthy processes, rigorous curation, and claims of a “human touch” are validated by non-platform institutions as “counterbalances” amidst the acceleration of digital content production. Theoretically, this study expands the Bourdieusian framework of the sociology of literature by demonstrating that habitus is not structural determinism, but rather a space of reflective negotiation capable of functioning as an epistemological filter against data colonization. Furthermore, these findings affirm that artistic autonomy need not arise from frontal resistance but can be constructed through the inhabitation of an in-between space that is both ethical and meditative. The research findings provide a cultural map for the sustainability of literary practices in the algorithmic era, while also offering an epistemological alternative for interpreting the creative process that is not confined to digital metrics or heroic narratives of resistance.